Saturday

December 20, 2014

December 20, 2014

Posted by **Ama** on Thursday, November 22, 2012 at 12:25am.

an = 3an − 1 + 9 and a1 = 2

- precalculus -
**Bosnian**, Thursday, November 22, 2012 at 1:41amIf yourexpression mean :

an = 3 a ( n − 1 ) + 9

a1 = 2

then

a2 = 3 a1 + 9 = 3 * 2 + 9 = 6 + 9 = 15

a3 = 3 a2 + 9 = 3 * 15 + 9 = 45 + 9 = 54

a4 = 3 a3 + 9 = 3 * 54 + 9 = 162 + 9 = 171

a5 = 3 a4 + 9 = 3 * 171 + 9 = 513 + 9 = 522

**Answer this Question**

**Related Questions**

Math - Find the first five terms of the sequence for which a1=5,and an+1=3an+1. ...

Discrete Math - Calculate R(4) where the recursively defined sequence R is ...

algebra 2 - A sequence is defined recursively by a1=1,an=(an-1+1)^2. Write the ...

calculus - A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)...

Calculus - A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)...

calculus - A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)...

Math - Write the first four terms of the sequence defined by the recursion ...

AP Calculus - Find the first 4 terms and the 8th term of the recursively-...

Algebra 2 Honors - Right now in my class i am learning about sequences and ...

Math - Find the first five terms of each sequence, defined by the given rule. An...